THE INFLUENCE OF HEDONIC SHOPPING MOTIVATION, PROMOTION AND PRODUCT QUALITY ON IMPULSIVE ONLINE PURCHASE OF FASHION PRODUCTS - Intan Nur Safitri; Sri Hartono; Istiqomah Istiqomah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
With the rise of social commerce, internet buying and selling is causing consumers to make illogical purchases without considering the product's implications or benefits. The word is also referred to as consumer attitude. Impulsive purchasing is one of the consumptive mindsets. Impulsive purchasing is common among consumer attitudes. Consumers engage in impulse purchasing when they make unplanned purchases of things. This study intends to examine the impact of Hedonic Shopping Motivation, promotion, and product quality on impulsive online purchases of fashion products made via the social commerce platform TikTok Shop in Surakarta. This research is quantitative in nature. This study's population consists of consumers who have purchased fashion items from the TikTok Shop at least twice. The sample size for this study is one hundred respondents. IDM SPSS Statistics 26 was utilized to process the data gathered via the questionnaire method. Data analysis approaches Hypothesis tests, classical assumption tests, tests of multiple linear regression, and determination coefficients. According to the findings of this study, Hedonic Shopping Motivation has a favorable and significant effect on impulsive purchases, as do promotion and product quality. Keywords: Impulse Buying, Hedonic Shopping Motivation, Promotion, Quality Product.